2021
DOI: 10.1136/bmjopen-2021-050766
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of lay consultation in symptoms and illness experiences in informal urban settlements of low-income and middle-income countries

Abstract: ObjectivesLay consultation is the process of discussing a symptom or an illness with lay social network members. This can have positive or negative consequences on health-seeking behaviours. Understanding how consultation with lay social networks works in informal urban settlements of low-income and middle-income countries (LMICs) is important to enable health and policy-makers to maximise its potential to aid healthcare delivery and minimise its negative impacts. This study explored the composition, content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Most Filipinos in our sample relied on recommendations from family and friends to improve their health and avoid getting sick. Previous studies have also demonstrated reliance on family and friends for health information, especially among older adults (Onuegbu et al., 2021). Similarly, older adults in rural Taiwan also resorted to seeking health support from family and friends (Chen, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Filipinos in our sample relied on recommendations from family and friends to improve their health and avoid getting sick. Previous studies have also demonstrated reliance on family and friends for health information, especially among older adults (Onuegbu et al., 2021). Similarly, older adults in rural Taiwan also resorted to seeking health support from family and friends (Chen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, seeking health information from family and friends is common in LIMCs. It is a way for individuals to obtain health information and practical resources to aid their health‐seeking decisions (Onuegbu et al., 2021). Our findings also support and further characterize the impact of social relationships on the health and healthcare‐seeking behaviours of people from other ethnic minority groups (Eley et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the known pathway of association between slum residence, access to health and health outcomes, some studies have explored the role of social networks in slum residence and its impact on health-seeking behaviour and health outcomes. A recent systematic review by Onegbu and colleagues [ 29 ] reported the frequent use of lay consultation (health advice seeking amongst personal networks) among slum dwellers and how it positively and negatively affects health-seeking behaviour and adherence to medical expert advice. At the peak of Ebola virus infection in countries like Liberia, social networks in slums were identified as one of the strongest means of receiving relevant information – both misinformation and those based on evidence [ 20 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is empirical evidence suggesting slum dwellers interact with personal network members including family, friends and neighbours during illness and obtain a range of resources 5 7 29 30. A recent systematic review demonstrated that lay consultation have positive and negative consequences on treatment seeking behaviours in slum settings of LMICs 31. However, there are evidence gaps on network characteristics, how personal networks and online networks are combined and how the network characteristics impact on personal health seeking decisions.…”
Section: Introductionmentioning
confidence: 99%
“… 5 7 29 30 A recent systematic review demonstrated that lay consultation have positive and negative consequences on treatment seeking behaviours in slum settings of LMICs. 31 However, there are evidence gaps on network characteristics, how personal networks and online networks are combined and how the network characteristics impact on personal health seeking decisions. Getting this evidence requires egocentric techniques, which are used in network studies to elicit information about a network from an ego (individual); this is lacking in slum studies.…”
Section: Introductionmentioning
confidence: 99%